1995
DOI: 10.1161/01.atv.15.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Dietary Cholesterol Are Associated With Modest Increases in Both LDL and HDL Cholesterol in Healthy Young Women

Abstract: We studied the effects of dietary cholesterol intake on lipid and lipoprotein levels in healthy young women (n = 13) who were otherwise eating an American Heart Association (AHA) diet. The study used a randomized, three-way crossover design to determine the effects of 0, 1, or 3 eggs added per day (dietary cholesterol range, 108 to 667 mg/d). Each of the three diets was eaten for 8 weeks, with a washout period between diets. Three fasting blood samples were obtained during the last 3 weeks of each diet period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 36 publications
3
43
0
Order By: Relevance
“…The increase in LDL cholesterol was greater in women than in men but indistinguishable when expressed per 1000 kcal/d [36]. Although the studies were not done contemporaneously, the greater response in women in this cholesterol-feeding study is in keeping with the data of Clifton and Nestel in men and women younger than 50 years of age, which could be due in part to a greater triglyceride drop with fat feeding [25].…”
Section: Triglyceridessupporting
confidence: 69%
“…The increase in LDL cholesterol was greater in women than in men but indistinguishable when expressed per 1000 kcal/d [36]. Although the studies were not done contemporaneously, the greater response in women in this cholesterol-feeding study is in keeping with the data of Clifton and Nestel in men and women younger than 50 years of age, which could be due in part to a greater triglyceride drop with fat feeding [25].…”
Section: Triglyceridessupporting
confidence: 69%
“…In adults, delayed postprandial clearance is associated with higher fasting triacylglycerol concentrations (6). Fasting triacylglycerol concentrations are generally lower in children than in adults (28,30). In view of the evidence for a role of delayed postprandial clearance as a risk factor for IHD, the question arises whether delayed postprandial clearance is also present at an early age in children, and if so, which metabolic characteristics predict abnormal clearance in children.…”
Section: Discussionmentioning
confidence: 99%
“…LDL-cholesterol concentrations were determined by using the Friedewald equation (27). Plasma retinyl palmitate concentrations were determined by reversed-phase HPLC essentially as described previously (10,28). Apo E genotyping was performed by using genomic DNA as described by Hixson and Vernier (29).…”
Section: Anthropometric Measurements and Laboratory Analysesmentioning
confidence: 99%
“…Estimating the absolute effect of dietary cholesterol on plasma lipoprotein concentrations has been difficult because of the high degree of variability in response among individuals (89). Nonetheless, in carefully controlled studies performed in healthy young males and females, it was demonstrated that for every additional 100 mg of dietary cholesterol, fasting plasma total cholesterol concentrations increased by 1.47 and 0.73 mg/dl, respectively, with parallel increases in LDL cholesterol and apoprotein B concentrations (90,91). Increased levels of the cholesteryl ester transfer protein were observed at the highest levels of dietary cholesterol in males but not females.…”
Section: Dietary Cholesterolmentioning
confidence: 99%